Using saturation effects in a nonlinear amplifying loop mirror for multilevel phase-preserving amplitude regeneration - Roethlingshoefer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2011 13th International Conference on, 2011)
The influence of amplifier gain saturation in nonlinear amplifying loop mirror on simultaneous phase-preserving regeneration of two power states has been studied. Numeri cal simulations have shown an improvement of up to 4 dB for the first, low-power state and 8 dB for the se cond high-power state. Compar ed to the linear amplifier case an improvement of 3 dB for the se cond power state has been achieved.
lhft_intern.bib::Roethlingshoefer2011a
Keywords: 2R regeneration; quadrature amplitude modulation; NALM; NOLM